A caça no Brasil: panorama histórico e atual - Ferreira, Hugo Fernandes (2014)
historical and current scenario. In Brazil, hunting is widely practiced throughout the territory since ancient times, causing dramatic environmental consequences, although there has never been a comprehensive analysis that addressed this issue at a national level under a conservation perspective. In summary, it is known that the Brazilian hunting is a problem, but no one knows for sure what it is, what its history and what the actual size of the problem. Thus, this research aims to analyze the hunting in Brazil and the historical, socioeconomic and cultural contexts associated with such activity, with the main focus on wildlife involved in different ways to human use, the techniques used for hunting and conservation implications associated with such uses, in a comparative analysis between different biomes. The manuscript was divided into two volumes. The first one deals with the historical aspect. In the Chapter I, the survey of official documents, paintings, accounts of natural history expeditions, scientific chapters, books and papers involving hunting in Brazil were conducted. It was possible to analyze the evolution of the use of the techniques; indigenous and European influences; data on regional extinction of species; preferences of game species for food consumption, among many other factors. In the Chapter II, we realized an historical survey and listed the changes of legislation and the perceptions of the national mass media involving hunting activities to establish if there is a correlation between these factors and what the possible consequences of these changes for wildlife conservation. We demonstrate that this correlation exists and has evolved interdependently. The second volume deals with the current situation and was accomplished through 529 interviews in 25 localities from 12 states and in all Brazilian biomes. The first chapter aimed to inventory, describe and categorize these techniques in all biomes. Moreover, further analysis on the Index of Cultural Significance of these strategies, which were discussed in regional and national levels have been proposed. Altogether, 39 techniques have been documented, described and categorized according to purpose, autonomy, lethality, selectivity of species and abundance of specimens captured. The Chapter II proposes to conduct an inventory of the wildlife hunting related in food purposes of rural communities in localities of all biomes of the country, through interviews and literature review. We documented 344 species, although our estimates indicate that this number could reach more than 525, where 46% are birds, 42% are mammals, 11% are reptiles and 1% is amphibians. The last chapter aimed to point out what is the region historically most impacted by hunting in Brazil, assuming the Northeast region as hypothesis. Data were quantified to calculate the Use of Frequency Value (UFV) and statistically analyzed with data from the biomass of each species cited in each area. The results indicate a national trend of high UFV’s for large species. This pattern is followed in the Amazon, Pantanal, Cerrado and Pampas. In contrast, the areas of the Atlantic Forest and mainly Caatinga, both in Northeastern Brazil, present the reverse of this pattern, indicating depletion and local extinction of large animals. This can be explained by the history of occupation, economic aspects, ecological support capacity, difficulty in livelihood alternatives and specific cultural patterns.